Early intervention, treatment and rehabilitation of employees with common mental disorders by using psychotherapeutic consultation at work: study protocol of a randomised controlled multicentre trial (friaa project) - Weber, Jeannette; Angerer, Peter; Brenner, Lorena; Brezinski, Jolanda; Chrysanthou, Sophia; Erim, Yesim; Feisst, Manuel; Hansmann, Marieke; Hondong, Sinja; Kessemeier, Franziska Maria; Kilian, Reinhold; Klose, Christina; et al. (BMC Public Health, 2021)
BackgroundCommon mental disorders are one of the leading causes for sickness absence and early retirement due to reduced health. Furthermore, a treatment gap for common mental disorders has been described worldwide. Within this study, psychotherapeutic consultation at work defined as a tailored, module-based and work-related psychotherapeutic intervention will be applied to improve mental health care.MethodsThis study comprises a randomised controlled multicentre trial with 1:1 allocation to an intervention and control group. In total, 520 employees with common mental disorders shall be recruited from companies being located around five study centres in Germany. Besides care as usual, the intervention group will receive up to 17 sessions of psychotherapy. The first session will include basics diagnostics and medical indication of treatment and the second session will include work-related diagnostics. Then, participants of the intervention group may receive work-related psychotherapeutic consultation for up to ten sessions. Further psychotherapeutic consultation during return to work for up to five sessions will be offered where appropriate. The control group will receive care as usual and the first intervention session of basic diagnostics and medical indication of treatment. After enrolment to the study, participants will be followed up after nine (first follow-up) and fifteen (second follow-up) months. Self-reported days of sickness absence within the last 6 months at the second follow-up will be used as the primary outcome and self-efficacy at the second follow-up as the secondary outcome. Furthermore, a cost-benefit assessment related to costs of common mental disorders for social insurances and companies will be performed.DiscussionPsychotherapeutic consultation at work represents a low threshold care model aiming to overcome treatment gaps for employees with common mental disorders. If successfully implemented and evaluated, it might serve as a role model to the care of employees with common mental disorders and might be adopted in standard care in cooperation with sickness and pension insurances in Germany.Trial registrationThe friaa project was registered at the German Clinical Trial Register (DRKS) at 01.03.2021 (DRKS00023049): https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00023049.
CRIS-Team WoS Importer:2021-07-23

Evaluation of a Group Therapy for Work-Related Mental Disorders - Hondong, Sinja; Morawa, Eva; Kastel-Hoffmann, Silke; Kandler, Anja; Erim, Yesim (International Journal of Environmental Research and Public Health, 2023)
Objectives: Work-related mental distress is one of the most dominant reasons for sick leave and early retirement. Specialized therapy programs for work-related mental health problems are rare, especially in a group setting. This study evaluates the severity of depression, anxiety, somatization and burnout symptoms before and after a work-related group therapy program. Methods: Patients of a psychosomatic outpatient clinic with work-related mental disorders completed 12 sessions of a manual-based group training with reference to the workplace. Data were collected using the Patient Health Questionnaire-9 (PHQ-9), Patient Health Questionnaire-15 (PHQ-15), General Anxiety Disorder Scale-7 (GAD-7) and the Maslach Burnout Inventory (MBI) before (T1) and directly after the intervention (T2). Results: Overall, 48 participants completed the intervention. The participants’ symptoms of depression (T1: M = 11.06, SD = 6.19, T2: M = 8.92, SD = 8.17; p < 0.001, d = 0.53) and anxiety (T1: M = 9.94, SD = 5.18, T2: M = 7.13, SD = 5.69; p = 0.001, d = 0.49) as well as their emotional exhaustion (T1: M = 4.63, SD = 0.95, T2: M = 4.05, SD = 1.35; p < 0.001, d = 0.55) decreased significantly, and the difference was clinically relevant at T2. For cynicism (T1: M = 3.93, SD = 0.99, T2: M = 3.70, SD = 1.32; p = 0.14, d = 0.22) and personal fulfillment at work (T1: M = 4.30, SD = 0.83, T2: M = 4.41, SD = 0.94; p = 0.24, d = 0.17), the difference between T1 and T2 was not significant. Women benefited more than men (PHQ-9: p < 0.001, d = 0.96; GAD-7: p < 0.001, d = 0.91; PHQ-15: p < 0.001, d = 0.76) from the training. Conclusions: Participants’ mental health symptoms were substantially reduced during the course of the work-related group therapy. As mental health problems account for the largest group of work disability days, the potential of group therapy should be better exploited in health care services.
CRIS-Team Scopus Importer:2023-02-24
Keywords: anxiety; burnout; depression; mental health treatment; work-related mental disorders

Implementierung einer psychotherapeutischen Sprechstunde am Arbeitsplatz (PT-A): Erwartungen, Bekanntmachung und Nutzung - Kohl, Fiona; Schröder, Ute B.; Stegmann, Ralf; Wegewitz, Uta; Hander, Nicole; Hansmann, Marieke; Angerer, Peter; Erim, Yesim; Hondong, Sinja; Kröger, Christoph; Mulfinger, Nadine; Waldman, Tamara; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2024)
Introduction: Psychotherapeutic consultation at work (PT-A) offers easily accessible, short-term support for employees experiencing psychological stress. The aim of the study was to evaluate aspects of the implementation regarding announcement, access, and use of the PT‑A. Methods: The study was conducted as part of a randomized controlled trial (RCT) called “Early Intervention in the Workplace”. Forty-six company actors answered a questionnaire about how the companies announced the PT‑A to their employees, the barriers in the announcement of the PT‑A, and the beneficial factors of using the PT‑A. The access routes of the 550 participating employees were used from the baseline data of the RCT. Seven company actors were qualitatively interviewed about their expectations of the PT‑A and 22 participants of the RCT were interviewed about their experiences accessing and using the PT‑A. Results: The company actors hoped that the PT‑A would have an impact on all levels of prevention. Most companies announced the PT‑A centrally (e.g., flyers and intranet) as well as through individual recommendations (e.g., through the company’s social counselling and occupational health professionals). Employees appreciated the opportunity to participate anonymously in the central announcement. Advantages of the supportive access were seen in the accessibility of employees without treatment experience, employees with high levels of suffering, and employees who have not yet recognized their own need for treatment. Discussion: The results suggest that it is useful to announce the PT‑A centrally to all employees but also to recommend it personally to affected employees. By using both methods, different PT‑A target groups can be reached and the advantages of anonymous participation are retained.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Early diagnosis; Mental health; Prevention; Psychosomatic consultation at work; Workplace health promotion

Psychische Gesundheit am Arbeitsplatz – Welche Rolle spielen sozioökonomische, geschlechterspezifische und migrationsbedingte Ungleichheiten? - Herold, Regina; Feißt, Manuel; Morawa, Eva; Hondong, Sinja; Rothermund, Eva; Waldmann, Tamara; Heming, Meike; Weber, Jeannette; Hander, Nicole R.; Mulfinger, Nadine; Kröger, Christoph; Erim, Yesim (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2024)
Background: Risk factors for mental health can be found in socio-economic-, gender- and migration-specific inequalities. These factors and the extent of depression, anxiety, and somatization among employees were examined in the present study. Methods: As part of the Early Intervention in the Workplace Study (friaa), mentally burdened employees at five locations in Germany were surveyed on socio-demographic-, work-, migration-, and health-related content. Regression analyses were used to examine the relationship between these factors and depression (Patient-Health-Questionnaire-9, PHQ-9), anxiety (Generalized Anxiety Disorder-2, GAD-2), and somatization (Somatic Symptom Scale-8, SSS-8) in the entire sample and in people with migration background (MB). For the latter, acculturation (Frankfurt Acculturation Scale, FRACC) and the perception of burden in terms of demands of immigration (Demands of Immigration Scale, DIS) were also taken into account. Results: On average, the 550 employees (12% with MB) showed clinically relevant depression (M = 13.0, SD = 5.1) (PHQ-9 ≥ 10), anxiety (M = 3.5, SD = 1.7) (GAD ≥ 3) and somatization (M = 13.0, SD = 5.8) (SSS-8 ≥ 12). Female gender was associated with higher anxiety and somatization. Older age and night shift work were associated with higher somatization. Discussion: The results confirm the high level of mental burden among this sample of employees in Germany. In order to maintain their mental health, support measures should be offered, especially for vulnerable groups such as women, older employees, and night shift workers.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Acculturation; Depression; Gender differences; Migration; Working conditions

Training emotionaler Kompetenzen - Berking, Matthias; Hondong, Sinja (Psychotherapie im Dialog, 2018)